Cholinergic Projections From the Pedunculopontine Tegmental Nucleus Contact Excitatory and Inhibitory Neurons in the Inferior Colliculus - Noftz, William A.; Beebe, Nichole L.; Mellott, Jeffrey G.; Schofield, Brett R. (Frontiers in Neural Circuits, 2020)
The inferior colliculus processes nearly all ascending auditory information. Most collicular cells respond to sound, and for a majority of these cells, the responses can be modulated by acetylcholine. The cholinergic effects are varied and, for the most part, the underlying mechanisms are unknown. The major source of cholinergic input to the inferior colliculus is the pedunculopontine tegmental nucleus (PPT), part of the pontomesencephalic tegmentum known for projections to the thalamus and roles in arousal and the sleep-wake cycle. Characterization of PPT inputs to the inferior colliculus has been complicated by the mixed neurotransmitter population within the PPT. Using selective viral-tract tracing techniques in a ChAT-Cre Long Evans rat, the present study characterizes the distribution and targets of cholinergic projections from PPT to the inferior colliculus. Following deposit of viral vector in one PPT, cholinergic axons studded with boutons were present bilaterally in the inferior colliculus, with the greater density of axons and boutons ipsilateral to the injection site. On both sides, cholinergic axons were present throughout the IC, distributing boutons to the central nucleus, lateral cortex, and dorsal cortex. In each IC subdivision the cholinergic PMT axons appear to contact both GABAergic and glutamatergic neurons. These findings suggest cholinergic projections from the PPT have a widespread influence over the IC, likely affecting many aspects of midbrain auditory processing. Moreover, the effects are likely to be mediated by direct cholinergic actions on both excitatory and inhibitory circuits in the inferior colliculus.